PPV-3 Evaluación antimicrobiana del extracto etanólico de raíz de cornezuelo (Acacia cornígera) - Cuahutenco Tlaxcaltecatl, Fátima; Bárcena Vicuña, Guadalupe Gabriela; Ramírez Hernández, Johana; Nava Montiel, Leonor; Reyes Jurado, Fátima (Revista Productos Naturales, 2022)
In recent years, there has been increasing awareness about microbial resistance, due to the problems that this brings to the health system in the country, as well as the need to find new therapeutic options that are accessible, economical and effective for the population.
Keywords: Acacia cornigera; microbial resistance; strains; antibiotics; plants